Policymakers' Logic on Islamic Banking: Islamic Banking as an Ethno-Political Tool in Malaysia. Issue 2 (August 2021) - Kitamura, Hideki
Social scientists have long sought to understand what Islamic banking is. This study seeks to answer this question by exploring the neoliberalisation process of Islamic banking policies in Malaysia and identifying policymakers' logic behind this process. For this purpose, this study conducted interviews with actors associated with Bank Negara Malaysia (BNM), the central bank of Malaysia. The findings demonstrate that, in the neoliberal era, BNM quietly and continuously pursued the goal of preferably giving economic opportunities to Malay Muslims by establishing institutional mechanisms rather than by offering preferential treatment in a straightforward manner. The Shariah nature of Islamic banking served to conceal this goal from the public. I define Islamic banking as an ethno-political tool rather than simply as a religious economy and contend that the philosophy of Islamic banking as a moral economy conceals an agenda of protecting Malay interests.